Software defined networking based load balancer / Fatma Nazihah W. Hashim - W. Hashim, Fatma Nazihah (2016)
As the number of network applications, devices and technologies used were increasing rapidly over the past years, resource control and network management are becoming challenging issues in maintaining network performance. Load balancing is crucial in order to allocate massive workload across many nodes in the network. Software Defined Networking (SDN) is a promising platform to build load balancer as it enables fast application deployment and delivery, thus reducing IT costs through policyenabled workflow automation. This paper focus on the design of a SDN based server load balancing application that will handle traffic load flowing into the system. The completed system is simulated on POX controller, an OpenFlow switch and three set of network topologies consisting the same number of hosts but different number of clients. Results show that round robin based load balancer yield better average response time and network bandwidth utilization, but shows^ tradeoff in the aspect of CPU utilization.